High-velocity impact on composite sandwich structures: A theoretical model. (1st July 2021) - Alonso, L.; Solis, A.
Highlights: A theoretical study is presented on woven E-glass fibre/polyester peels and PVC foam core. The energy-based theoretical model predicts the ballistic response of sandwich structures. New physical hypotheses are introduced to accurately describe the impact phenomenon stages. The relative roles of failure mechanisms are studied. Graphical abstract: Abstract: A theoretical energy-based model to capture the ballistic response of sandwich structures made of composite material peels and a crushable foam core was developed. The model was based on the wave propagation theory and it was split in six stages with their corresponding energy-absorption mechanisms. The division of the stages was based on the physical interpretation of the perforation process involving reasonable hypotheses and simplifications. The energy-absorption was analysed at velocities below, near and above the ballistic limit within all the stages showing the general trends in terms of their relative importance. The time and velocity at each stage was separately analysed within a wide range of velocities in order to see the stage contribution to the energy-absorption. The model was validated against experimental results obtained in the literature showing a good agreement in terms of the impact-residual velocity curve.